Nutritive value of forages as affected by soil and climatic differences - Clary, F.G.; Brent, B.E.; Richardson, D.; Banbury, Evans E; Spaeth, C.W.; Erhart, A.B.; Arnett, D.W.; Boren, Fred W.; Perry, H.B. (Kansas State University. Agricultural Experiment Station, 2011)
Wintering and finishing performances of beef steers have been compared at Colby, Garden City, Manhattan and Mound Valley. When feeds were grown locally, cattle at Garden City and Colby outperformed those at Manhattan and Mound Valley (Bulletin 507, 1967). Since all cattle were of the same origin, differences were credited to the climate and/ or feed composition. In 1968-9 (trials 5 and 6), cattle were fed at all locations on feed produced at Garden City. During the wintering phase in trial 5, cattle at Colby and Garden City significantly outgained those at Mound Valley (P<.0l). Performance at Manhattan was intermediate. In trial 6, table 18, during wintering, steers at Manhattan gained faster (P<.01) than those at Colby or Garden City but not those at Mound Valley. Finishing gains did not differ significantly in either trial. Results of the last two tests being more uniform than results of the previous four indicates some of the differences are from the site where the feed is produced.
Keywords: Beef; Soil; Climate; Wintering performance; Finishing performance